Hubungan Pola Makan dan Aktivitas Fisik dengan Status Gizi Siswa Kelas VIII SMP Negeri 19 Palu - Asifah, Nur; Laenggeng, Abd. Hakim; Lilies, Lilies; Kundera, I Nengah; Masrianih, Masrianih; Ashari, Abdul (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the relationship between diet and physical activity with the nutritional status of students of SMP Negeri 19 Palu. This study used a cross sectional design with a quantitative approach and analytic observational type. The subjects were 77 students of class VIII (aged 13-15 years) who were selected using simple random sampling technique. Data were collected using FFQ (Food frequency Questionnaire) to assess diet and APARQ (Adolescent physical Activity Recall Questionnaire) for physical activity, both validated instruments from previous studies. As well as anthropometric measurements (height and weight) using the Body Mass Index (BMI) to determine nutritional status. The results of the analysis using the chi-square test showed that there was a significant relationship between diet and nutritional status (Ï‡Â²(3) = 8.772; p = 0.032), and between physical activity and nutritional status (Ï‡Â²(4) = 9.919; p = 0.042) Respondents with a good diet and moderate to vigorous physical activity tended to have normal nutritional status, while poor diet and light physical activity were more common among students with abnormal nutritional status. These findings suggest that diet and physical activity play an important role in determining the nutritional status of adolescents. The implications of this study emphasize the importance of educational intervention programs in the school environment to support healthy lifestyles and prevent nutritional problems among students.